Peningkatan Literasi Anak Usia Dini melalui Pendampingan Calistung di Taman Kanak-Kanak - Nuramaliyah, Nuramaliyah; Mikhratunnisa, Mikhratunnisa; Oryza Safitri; Lukmanul Hakim; Diah Anggeraini Hasri; Amry Purnama Mauladi; Fitriyantari (Abdimas Indonesian Journal, 2025)
This community service aims to improve early childhood literacy through Calistung (Reading, Writing, and Counting) mentoring using the card method in Kindergarten. The card method is used to help children recognize letters, numbers, and improve reading and writing skills interactively. Mentoring activities are carried out by introducing various letter, number, and picture cards that are in accordance with the material being taught. Mentoring is carried out in a fun way through games and movements that involve the active participation of children. The evaluation results show that children have improved in recognizing letters, numbers, and reading and writing skills. This program has also succeeded in increasing children's motivation to learn in a fun way. With a visual approach and games, children find it easier to understand basic literacy concepts. Mentoring using the card method has proven effective in improving basic literacy skills in early childhood, creating a positive learning atmosphere, and supporting children's cognitive development